2018
DOI: 10.3399/bjgp18x695057
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of regional variation of opioid prescribing in primary care in England: a retrospective observational study

Abstract: Long-term opioid prescribing is increasing despite poor efficacy for non-cancer pain, potential harm, and incompatibility with best practice. Questions of equality of care arise from higher prescription rates in the north of England and in areas of greater social deprivation. A national registry of patients with high opioid use would improve patient safety for this high-risk demographic, as well as provide more focused epidemiological data regarding patterns of prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
132
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(150 citation statements)
references
References 40 publications
17
132
1
Order By: Relevance
“…15 Despite these guidelines, there remains substantial variation in the practice of prescribing opioids. [19][20][21] Although other studies have examined large-scale variations, [22][23][24][25] little is known about the patient-and clinician-specific factors associated with any opioid and chronic opioid prescribing in primary care. The reliance in these studies on claims data limited the examination of patient, clinician, and practice characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…15 Despite these guidelines, there remains substantial variation in the practice of prescribing opioids. [19][20][21] Although other studies have examined large-scale variations, [22][23][24][25] little is known about the patient-and clinician-specific factors associated with any opioid and chronic opioid prescribing in primary care. The reliance in these studies on claims data limited the examination of patient, clinician, and practice characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, left-behind regions experience disproportionate levels of premature mortality (Plümper et al 2018). Mordechai et al (2018) have identified higher opioid prescription rates in the north of England and in areas of greater social deprivation. The highest incidence of relative urban decline is primarily located in Northern England (Pike et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number of opioid analgesics prescribed in the UK for non-cancer pain over the past few years is on a steadily upward trajectory. 1 Alongside this, the numbers of deaths reported to involve opioid analgesics are rising as well. 2 There are concerns that there may be some echoing of the situation in the US where overdose deaths from prescription opioids are a major issue.…”
Section: Introductionmentioning
confidence: 99%